(3GNJUGU GdeMGce GdYScQjI aj EWGQ bGfhf GdbVGA GdYScQj Qbe (B16 (3dSfI (B2007 (3h JYOjdGJg (B/ s - (3YeQh eMeO Mdejs; (3CSGeI MSfjf YHjO s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2012)
(3YGdLJ GdOQGSI GdehVhY aj KdGKI CHhGH(B: (3aJcde GdHGH GdChd Yf (B( (3MOhO GNJUGU GdeMGce GdYScQjI (B): (3JfGhd GdaUd GdChd Yf SQjGf GNJUGU GdeMGce GdYScQjI ef GdfGMjI GdTNUjI(B: (3h aj GdaUd GdKGfj Yf SQjGf GNJUGU GdeMGce GdYScQjI ef fGMjI GdecGf(B: (3SQjGf GNJUGU GdeMGce GdYScQjI ef GdfGMjI GdYjfjI(B. (3h aj GdHGH GdKGfj JfGhd GdMOjK (B( (3eGgjI GNJUGU GdeMGce GdYScQjI (B) (3NUU GdaUd GdChd ddMOjK Yf CfhGY GdeMGce GdYScQjI h JTcjdgG(B: (3h GdaUd GdKGfj dGNJUGU GdeMGce GdYScQjI HfXQ GdLQGFe h GdaUd GdKGdK Je ajg SQO GdeHGOF GdYGeI deHGTQI GdeMGce GdeYScQjI GNJUGUgG(B: (3h GdaUd GdQGHY dGNJUGU GdeMGce GdYScQjI ai MGdI GdWhGQFs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFjs
(3HHdjhLQGajG(B: (3UaMGJ (B157-163s
Keywords: (3GdLPhQ GdJTQjYjI ddeMGce GdYScQjIs; (3JejjR GdeMGce GdYScQjI Yf GdeMGce GdLfGFjI GdYGOjIs; (3GNJUGU GdeMGce GdYScQjI ef fGMjI GdReGfs; (3GNJUGU GdeMGce GdYScQjI ef GdfGMjI GdTNUjIs; (3GNJUGU GdeMGce GdYScQjI ef fGMjI GdecGfs; (3GNJUGU GdeMGce GdYScQjI ef GdfGMjI GdYjfjIs; (3CfhGY GdeMGce GdYScQjIs; (3GdeHGOF GdYGeI deHGTQI GdeMGce GdYScQjI GNJUGUgGs; (3GNJUGU GdeMGce GdYScQjI aj MGdI GdWhGQFs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs